Pengaruh Rekrutmen dan Kompensasi Terhadap Kinerja Karyawan dengan Pengawasan Kerja Sebagai Variabel Moderating pada PT. Titian Abadi Lestari - Ari Soeti Yani; Rinaldo Rinaldo (Majalah Ilmiah Bijak, 2017)
This research about "Effect of Recruitment and Compensation against Employee Performance with Monitoring of Work as Moderating Variables at PT. Titian Abadi Lestari ". The dependent variable in this research is the employee's performance. Independent variable is the recruitment and compensation. As well moderating variables in this research is monitoring of work. Population and sample in this research is all employees or as many as 70 people. The analysis method used in this research is to test the feasibility of the data, test hypotheses and test moderating variable. Test result of Feasibility data proves the questionnaire is valid and reliable. While testing the hypothesis partially and simultaneously prove that the recruitment and compensation jointly and significant positive effect on employee performance. The test results proved that the moderating variable the monitoring of work is pure moderating because of the effect results Z to Y on the first output and the effect of the interaction Z * X1 on the second output, one of them is significant. So monitoring of work affect recruitment and compensation moderating on employee performance.